On the application of ergodic theory to alternating Engel series - C. Ganatsiou (International Journal of Mathematics and Mathematical Sciences)
We investigate the ergodic behaviour of the basic operator which generates the modified Engel-type alternating series representations of any number in (0,1] in terms of rationals.